2004
DOI: 10.1007/s10763-004-1951-z
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Conceptions in Animal Classification Focusing on Amphibians and Reptiles: A Cross-Age Study

Abstract: This study examined students' alternative conceptions of reptiles and amphibians and the extent to which these conceptions remain intact through the elementary (grades 4 and 6), junior, and senior high school years. We administered multiplechoice and free-response instruments to a total of 513 students and interviewed at least 20 students at each educational level to get an in-depth view of their original conceptions. Then, we developed and administered a two-tier multiple choice diagnostic instrument to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 21 publications
6
30
0
10
Order By: Relevance
“…If students were to rate their attitude toward amphibians, they could be wrongly thinking about turtles -reptiles or only frogs -the prototypical species for amphibians (Yen et al, 2004). The instrument was in a form of a questionnaire and consisted of two parts.…”
Section: Instrumentmentioning
confidence: 99%
“…If students were to rate their attitude toward amphibians, they could be wrongly thinking about turtles -reptiles or only frogs -the prototypical species for amphibians (Yen et al, 2004). The instrument was in a form of a questionnaire and consisted of two parts.…”
Section: Instrumentmentioning
confidence: 99%
“…These alternative conceptions may resemble the ideas of previous generations of natural philosophers; they are products of direct observation, everyday language, the mass media and peer culture and they are found frequently amongst teachers as well as students (Munson, 1994;Yen, Yao, & Chiu 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Randler et al (2007) found an increase in knowledge about animals with the age of respondents, but in their research there was no signi cant di erence in results between genders. Yen et al (2004) showed that pupils and students had problems with amphibians and reptiles in their research. The turtle was classi ed as an amphibian by a signi cant percentage of students; the reason was due to its aquatic and terrestrial habits.…”
Section: Research In the Eld Of Misconceptionsmentioning
confidence: 99%